Sleep duration and sleep quality as season-long predictors of ratings of perceived exertion and psychological wellbeing in female soccer athletes - Camargo, M. E.; Cheever, K. M. (International Journal of Exercise Science Conference Proceedings, 2025)
Sleep is a critical factor in optimizing athletic performance and well-being. Sleep effects on physiological and psychological well-being have been examined through cross sectional studies, but limited research exists on the longitudinal impact that sleep has on well-being in collegiate athletes.